2020
DOI: 10.3390/nu12040979
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Drivers of Fresh Citrus Fruits in Urban Italy: Is It All about Taste?

Abstract: While the medical community supports the growth of citrus consumption as part of a healthy diet, there is limited knowledge about consumer preferences for these fruits. The current study analyzed the purchasing patterns and drivers of fresh citrus fruits from a convenience sample of 346 Italian food shoppers. Results revealed that clementines were the citrus fruit purchased most, followed by oranges and tangerines. Sweetness and smell were important product attributes for respondents. Different drivers affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The interviews took place in three different regions of Italy lasting around ten minutes. The respondents were randomly recruited while shopping in large-scale retail hypermarkets [ 35 , 36 ] in the cities of Turin, Milan, and Reggio Calabria. In-store interviews were directly carried out using a specific questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…The interviews took place in three different regions of Italy lasting around ten minutes. The respondents were randomly recruited while shopping in large-scale retail hypermarkets [ 35 , 36 ] in the cities of Turin, Milan, and Reggio Calabria. In-store interviews were directly carried out using a specific questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that the preference for conventional production in this cluster could be caused by intrinsic attributes of clementines: being protected by a thick peel, this fruit is probably always considered by consumers as not hazardous, as the peel protects it by residues of chemical compounds. Consistently, the general perception among consumers of clementines and other citrus fruits is that they are a very healthy food (Di Vita et al, 2020;Iofrida et al, 2019). Taking into consideration other agri-food products, our research is consistent with the cluster identified by Massaglia et al (2019), which revealed how some consumers attached importance to high-quality and high-priced products, while they were not interested in sustainability and origin attributes.…”
Section: Discussionmentioning
confidence: 94%
“…The conjoint analysis is a widespread method in consumer research, often adopted to quantify the utility of consumers for food product attributes (Schnettler et al, 2009;Saba et al, 2010;Di Vita et al, 2019). The three selected attributes were identified as the most relevant in consumer clementines' choice, based on market data analysis and review of recent scientific literature (Di Vita et al, 2020;RRNb, 2020;Verain et al, 2020). The price levels were chosen according to the average clementine prices observed in different retail stores in Turin and Milan, at the time of the research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre-test was necessary to verify the questions were complete and effective and to make corrections to the questionnaire possible. Data were collected in the metropolitan areas of Milan and Turin, which are considered as representative of northern Italian urban areas (Di Vita et al , 2020). The interviews were carried out from Monday to Saturday between 10.00 a.m. and 3.00 p.m., with an average time per interview of between 10 and 15 min.…”
Section: Methodsmentioning
confidence: 99%